The dorling kindersley geography of the world - Peach, Susan; Greenwood, Marie (Dorling Kindersley London, 2003)
Our planet is explored from country to country in this book. It examines social issues from world religion to natural disasters. The use of 3-D maps, colour photographs, flags, charts, and diagrams help to bring the the world to life.